THE SAVING AND EARLY DICHARGE OF A NEONATE WITH SEVERE MECONIUM ASPIRATION SYNDROME - SIVADASAN, MRINAL; Dinaraj, Archana; S, Bhavya; Indumathi, Kristin (Indian Journal of Case Reports, 2022)
Animal experiments have shown the resolution of radiological infiltrates of meconium aspiration syndrome (MAS) after using surfactant lavage. Intra-tracheal instillation of surfactant, as well as surfactant lavage, is studied in MAS. However, INSURE (INtubation, administration of SURfactant, Extubation) is never reported to have been used for meconium aspiration syndrome although it is used as the standard method of delivery of surfactant for respiratory distress syndrome. This is a case report of the use of INSURE technique for severe Meconium Aspiration syndrome. The baby was born at term gestational age to a primigravida mother by C-section for fetal distress. The baby was vigorous with chest retractions. Hence baby was supported with delivery room Continuous positive airway pressure (CPAP) and shifted to Neonatal Intensive Care Unit (NICU). In NICU, the baby was stabilized and given surfactant using the INSURE technique. Subsequently, a Chest X-ray showed clearing of lung infiltrates and drastically reduced oxygen requirement of the baby and the baby was discharged early to home.